Les missiles de croisière soviétiques aéroportés et la géopolitique de la défense aérienne de l’Amérique du Nord : Une nouvelle perspective du Nord canadien - Haglund, David (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1988)
Recent developments in the technology of weaponry have brought about a reconsideration of the "geopolitical" importance of Canadian northern spaces to the physical-security interests of the two superpowers, and especially of the United States. Those technological developments have been apparent in three areas : ballistic missile defence (BMD), nuclear-propelled (and sometimes-armed) submarines, and air-launched cruise missiles (ALCM). Both the BMD and nuclear-submarine issues have generated much debate of late in Canada ; considerably less attention has been accorded the analysis of developments in the domain of the ALCM. It is with this latter weapon-system and in particular with the manner in which Washington regards Soviet ALCMs, that this article is concerned. Argued here is the view that the perceived Soviet ALCM threat has been of major importance in the recent modernization of North American air-defence Systems. In addition to discussing the development and consequences of Soviet ALCMs, this article also explores the extent to which technological transformations in weapons-systems might also have the effect of achieving conceptual transformations in strategic analysis. A major sub-theme of the article is the contention that technological variables have been occasioning a reconsideration of the manner in which theorists of international relations and strategic studies have been assessing the relationship between geographical configuration and the perceived strategic significance of states. The article observes that the once-moribund field of "geopolitics" has been undergoing a modest revival among theorists, in part because of changes in those weapons technologies in discusses.